Light quality affects the proliferation of in vitro cultured plantlets of Camellia oleifera Huajin - Chaoyin He; Yanling Zeng; Yuzhong Fu; Jiahao Wu; Qin Liang (PeerJ, 2020)
Background Camellia oleifera is an important oil-yielding woody plant native to China. Tea oil extracted from the seeds is rich in health-beneficial compounds. Huajin is a high-yielding elite variety of C. oleifera, with large fruits and remarkable resilience, widely cultivated in southern China; however, its seedling quality tends to be uneven. At present, techniques such as grafting, and cuttings are primarily adopted to propagate C. oleifera. These approaches are susceptible to environmental constraints owing to the long growth period, resulting in the lack of C. oleifera seedlings. Methods to make the cultivation more economical are warranted; this can be facilitated by tissue culture technology to provide good-quality seedlings in a short time. Methods In vitro cultured plantlets of C. oleifera Huajin were exposed to red light (RL), blue light (BL), red:blue light at a 4:1 ratio (R4:B1), and red:blue light at a 1:4 ratio (R1:B4); white light (WL) was used as the control treatment. To investigate the influence of light spectral quality on the proliferation coefficient, photosynthetic pigments, soluble proteins, plant height, leaf shape, Rubisco enzyme activity, and stomata and leaf anatomical features. Results The highest proliferation coefficient was observed under combined red and blue (4:1) light. In addition, this treatment resulted in the second highest chlorophyll content, the thickest palisade and spongy tissues, and consequently, the thickest leaves. The same treatment resulted in the second highest stomatal density, albeit concomitantly with the smallest average stomatal length and width. Discussion These results indicate that high-quality propagation of Huajin shoots can be achieved by culturing the plants in vitro under a combination of red and blue (4:1) lights. Previous studies have shown that red and blue lights improve rooting and transplanting rates of tissue culture seedlings. Hence, future research should focus on the effect of light quality on rooting and transplanting of tissue culture plantlets of Huajin and its specific molecular mechanisms.